1994
DOI: 10.22358/jafs/69842/1994
|View full text |Cite
|
Sign up to set email alerts
|

Heat production in growing pigs fed rapeseed meal with various glucosinolate contents

Abstract: Two experiments were carried out on 48 growing Polish Landrace pigs, from 30 to 60 kg liveweight. Diets were composed of barley supplemented with rapeseed meal (RSM) or milk powder (C). Rapeseed meal contained 6.6 (RSM-7) or 24.3 ^moles (RSM-24) total glucosinolates per gram fat-free dry matter. In each experiment the animals received the same amount of metabolizable energy and lysine. Glucosinolate intake was different, however: 0 or 3.2 moles in experiment 1 and 3.2 or 10.9 moles per day in experiment 2. Ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…We previously found similar changes in our own studies (Fandrejewski et al, 1994;Raj et al, 1990) as have others (e.g. Thomke, 1984).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We previously found similar changes in our own studies (Fandrejewski et al, 1994;Raj et al, 1990) as have others (e.g. Thomke, 1984).…”
Section: Resultssupporting
confidence: 92%
“…A study of the use of rapeseed meal (RSM) in the feeding of pigs (Fandrejewski et al, 1994) showed that animals fed a diet containing RSM had a tendency to increased heat production.…”
Section: Introductionmentioning
confidence: 99%
“…In pigs fed RSM together with RS, the increase in thyroid, liver and kidney weight and decrease in secretion of T 3 and T 4 were not, however, directly proportional to GL intake. In comparison with the results of our previous experiments (Chabiera et al, 1994;Fandrejewski et al, 1994) on feeding RSM to fattening pigs, a weaker goitrogenic response to an increase of the GL level in the ration was found (from 2.1 to 7.3 mM/d). This was all the more surprising since along with the seeds, myrosinase (Bille et al, 1983a) was probably also introduced into the digestive tract of the animals.…”
Section: Discussionsupporting
confidence: 60%
“…This was accompanied by hypertrophy of the thyroid gland, liver and kidneys in all animals, even those in group RS-0. In spite of the lack of the control group fed on rape-free diet in this experiment, this statement can be based on previous experiments by Fandrejewski et al (1994) carried out on pigs from the same herd, in which a high dependence between thyroid and internal organ size and glucosinolate intake of animals was found. It was calculated that the weight of the pigs in group RS-0, receiving the least GL (2.1 mM/d) was also elevated (by about 30% in comparison to animals that did not receive glucosinolates).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation